Intra-articular drug injections in the combination treatment of rheumatic diseases - Yu. A. Olyunin (Современная ревматология, 2015)
In clinical practice, intra-articular injections of glucocorticoids (GC) are widely used to treat chronic joint inflammatory diseases, osteoarthritis (OA), and extra-articular soft tissue involve-ment. GCs given to patients with chronic arthritis may rapidly suppress joint inflammatory changes and ensure significant clinical improvements well before there is a benefit of prescribed disease-modifying antirheumatic drugs. According to the clinical features of disease, GCs may be used for systemic or local treatment in each specific case and a combination of these two treatments may be performed in some patients. In OA patents, the effect of intra-articular GC injections is less sustained than in those with joint inflammatory diseases and it persists for an average of about 3 weeks. Intra-articular hyaluronic acid is likely to be a more promising treatment for OA. It may also relieve pain considerably and improve joint functions. At the same time the highest effect was noted between weeks 5 and 13 after injection, but improvement also persisted after 14–26 weeks or longer in a number of cases.